The Intellectual Capital Components on Firm Value: Evidence from LQ-45 Index Companies - Eristy Minda Utami (Jurnal Keuangan dan Perbankan, 2018)
The purpose of this research is to analyze the influence of Intellectual Capital components on the firm value. Data used in this research is secondary data with the sampling method is purposive sampling. The population of this study is companies listed in LQ 45 period 2012 - 2015, then selected to be sampled in these study as many as 96 companies are observed. The analytical tool to test of hypothesis is multiple regression analysis. The result of Value Added Capital Employed (VACA) affects the firm value. This means that information about the efficient use of capital employed is captured by the market (investor) so as to affect the firm value, Value Added Human Capital (VAHU) affect the firm value, because the company has the best employees with a ratio perpendicular to the cost incurred by the company, get a lot of value added on them. Structural Capital Value Added (STVA) does not affect the firm value. This shows that the company's operational systems, organizational culture, management philosophy and all forms of intellectual property owned by the company are inefficient and economical in creating added value for the company.JEL Classification: G32; J24; O34DOI: https://doi.org/10.26905/jkdp.v22i2.1648